(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We develop a New Homotopy Perturbation Method (NHPM) in this paper to track down the informative arrangements of linear and non-linear Telegraph Equation. By utilizing the NHPM, it is plausible to get the semi-analytical arrangement or a closed structure assessed answer for an issue uncovers significant focuses. The calculation of models shows the straightforwardness and less control in contrast with the typical technique. The 3-dimesion graphical portrayals of linear and non-linear telegraph equations are likewise given to verify that numerical model. The MATLAB programming is utilized to address the 3-dimension and 2 dimension graphical arrangement of Telegraph condition and examine the arrangement found from NHPM.